Wheeled Robot Automated System Through Communication with Referee Box Using Base Station - Prasetyo, Okki; Puriyanto, Riky Dwi (Signal and Image Processing Letters, 2022)
Manual control of the robot makes the movement of the wheeled KRSBI robot inflexible and does not depend on time. This research can answer these problems. The robot can immediately know the command from the Referee box. In this final project, the author develops a communication system for the Base Station application. The communication system via WLAN at the base station uses a TCP (Transmission Control Protocol) communication system. At the Base Station which was developed with a GUI design to make it easier to control the robot. From the results of research conducted by the Base Station, referee boxes and robots can be well connected with the addition of the X, Y and angle data transmission features on the robot that are displayed on the Base Station. 2 meters is 0.045 ms, for transmission time with a distance of 4 meters is 0.049 ms, for transmission time with a distance of 6 meters is 0.048 ms, for transmission time with a distance of 12 meters is 0.049 ms, and for transmission with a range of 15 meters of 0.050 ms.